Dissipative soliton resonance in a passively mode-locked praseodymium fiber laser - Ahmad, Harith; Aidit, Siti Nabila; Tiu, Zian Cheak (Elsevier, 2019)
Dissipative soliton resonance (DSR) operation in a passively mode-locked praseodymium-doped fluoride fiber laser with a nonlinear optical loop mirror is proposed and demonstrated. A praseodymium-doped fluoride fiber is employed as the gain medium to allow lasing in the 1.3 μm region, and a stable square pulse emission at 1303 nm is observed. The width of the square pulse broadens with the increment of pump power, from 83 ns to 239 ns, whereas the peak power remains at a comparable level. The highest single pulse energy is recorded at around 2.3 nJ without the appearance of pulse breaking, validating the predicted DSR operation. To the best of author's knowledge, this work is the first study of DSR operation in the 1.3 μm region.